PEMANFAATAN APLIKASI MOBILE BERBASIS IOS DALAM MENUNJANG USAHA WEDDING ORGANIZER - Nur Ani; Muhammad Rizky Novaldi; Muhamad Ega; Tio Mafaza (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
Everyone wants to make their wedding receptions a very special day and give a moment that will not be forgotten in his life, so that the preparation and planning are ripe in making a plan to Provide the required results. But such high activity and mobility are a constraint to prepare such an important event that it does not maximize what is planned. PT H2O Planner is one of the wedding organizer who currently wants to improve the quality of the service provided. By providing mobile-based applications as one of the media in offering the services provided. PlanYourDays is a mobile based application created based on the needs of PT H2O Planner, using the prototype development method in the creation of this application. So that the application is produced according to the needs and desires of PT H2O Planner and can answer the problems of activity and mobility One obstacle in preparing for a wedding.